ANALYSIS OF TOTAL ASSETS AND SHORT-TERM LIABILITIES TOWARDS THE CONTRIBUTION OF ZAKAT FUNDS IN SUPPORTING SDG'S PROGRAMS (EMPIRICAL STUDY OF COMPANIES LISTED ON THE IDX) - Muhammad Fidiandri Putra (Edusight International Journal of Multidisciplinary Studies, 2025)
Indonesia's commitment to supporting the Sustainable Development Goals (SDGs) is important because the SDGs are the basis for the government and society's efforts to achieve sustainable development until 2030. Indonesia's commitment to the SDGs is closely related to the national development vision, which includes inclusive economic growth, reducing gaps, protecting the environment, and good governance. The research method uses multiple linear regression analysis with Eviews 9 to see how much influence the total assets and short-term liabilities variables have on the potential value of zakat on companies from the Energy, Raw Goods, Industrial, and Primary Consumer sectors. Non-Primary Consumers, Health, Finance, Property, Technology, Infrastructure, and Logistics Transportation are listed on the Indonesia Stock Exchange (BEI). The regression model has a strong relationship with the dependent variable, total zakat potential (R = 0.947), and the model explains around 89.73% of the variance in the dependent variable (R² = 0.897). The model obtains Y = 7050 - 0.00015X+ 0.0010X², where constant (7050): Value of Y (Zakat Potential) when increased by 1 unit, and Coefficient X² of Short Term Liabilities (0.0010) with an increase in Y of 0.0010 units when X² increases by 1 unit.